(untitled) - Stottrup, Josianne G. (Oxford, UK, 2003)
Text provides information on feeding of cultivated fish and shellfish. Covers in detail the biology and culture of the main live prey and microalgae used as feeds in the aquaculture of major commercial species including shrimps, sea bass, halibut, cod and bivalves. For fish farmers, researchers, and personnel in feed and equipment companies supplying the aquaculture trade.
Dinh dưỡng và thức ăn thủy sản
Keywords: Marine fishes; Feeding and feeds